Practical psychometrics a guide for test users - Lovett, Benjamin J. (New York The Guilford Press, 2023)
"I wrote this book to fill a gap-to try to explain the basics of psychometrics to the people who need that understanding most: test users. Professionals such as school psychologists, special educators, counselors, speech-language pathologists, and social workers sometimes administer tests and scales, or review evaluation reports with test data, and need to make sense of the test scores that they see. The book's content is (a) accessible, (b) intuitive, (c) concise, (d) clinically relevant, and (e) technically accurate"-- Provided by publisher.
"This is the first practitioner-oriented guide to basic psychometrics--the science behind test construction and validation. It is an essential course text and clinical reference for anyone who needs to select and administer diagnostic tests or review test score data obtained by others. Without assuming any mathematical background, the author describes the fundamentals of diagnostic testing, how to interpret score data, and how specific tests are used in school psychology, special education, counseling, and other contexts. Concepts such as reliability, validity, and fairness and test bias are explained in an accessible, conversational way. Detailed case examples illustrate the dos and don'ts of presenting test score data to clients, parents, and teachers in oral feedback and written reports. Pedagogical Features: *End-of-chapter exercises that emphasize application and understanding, with answers at the end of the book. *Key terms are bolded throughout and accessibly explained in the end-of-book glossary. *Resource appendix--annotated guide to articles and books on more advanced topics in psychometrics, assessment, and testing. "-- Provided by publisher.
Includes bibliographical references (pages 193-196) and index.
Keywords: Psychometrics